Efforts to Overcome Student Difficulties in Function Continuity Material Through The Use Of Structured Worksheets - Purbaningrum, Kus Andini; Sukmawati, Rika (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
This study aims to overcome students' difficulties in understanding the material continuity of functions through the use of structured worksheets in differential calculus courses. The research subjects were second semester students of the Mathematics Education Study Program, Faculty of Teacher Training and Education (FKIP), University of Muhammadiyah Tangerang (UMT). This type of research is Classroom Action Research which is carried out in two cycles where each cycle consists of two meetings. Continuity of Function material consists of several parts, namely set intervals of numbers, limits of functions and graphs, function continuity tests. The data obtained in this study are the activities and abilities of students in understanding the material. Student activity data was obtained by observing while student abilities were obtained by using a student understanding ability test. Furthermore, the data collected in this study were analyzed by descriptive analysis. Results analysis was carried out in each cycle to determine the success of using structured worksheets in overcoming student difficulties. The percentage of students who experience difficulties in cycle 2 is 26.92%. This figure is in a weak qualification with a range of 20% - 40% of the number of students, thus indicating success in this classroom action research. Thus the use of structured worksheets can overcome students' difficulties in understanding the continuity of functions material.